Prevalence of Pelvic Girdle Pain in Post Partum Women - Shraddha Dhongade1 , G. Varadharajulu2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Pelvic girdle pain is frequently reported musculoskeletal disorder in pregnant women. Thecondition is complex and underlying mechanism is unclear. Onset of pain is usually at 14-30 weeks ofgestation.Pregnancy hormones soften and stretch the ligaments of the body allowing the pelvis to open slightly duringlabour thus allowing easier passage. This leads to less stable pelvis. Women experiences reduced capacityfor activities such as standing, walking and sitting.PGP results in greater disability in pregnant women.Pelvic instability and pain due to increased lumbar, thoracic and pelvic mobility due to secretion of relaxinhormone lead to increased ligament laxity and there is slightly larger range of movement in the pelvic joint.[3]PGP is diagnosed on the basis of site of pain and ability to the pain by using the pain provocation tests. PGPis managed conservatively by a multidirectional team. It include addressing the psychosocial implication forthe women and family. Approach should be implemented for activity modification , pelvic support garments,manage acute exacerbations, physiotherapy and exercise program to prevent progression of symptoms.Objective: To find out the prevalence of pelvic girdle pain in post partum women.Method: An observational study was carried out using a cross sectional study design. The study wasconducted in the city of Karad, Maharashtra. Study was conducted using a sample size of 64 post partumwomen for a period of 6 months. The inclusion criteria was 20-40 years of females were included who werehad FTND. Exclusion criteria was obese females, pre pregnancy low back pain, women with high risk ofpregnancy and any kind of trauma to pelvic during pregnancy.Results: The results showed that 60.93% women have pelvic girdle pain during their post partum period byusing FABER, P4 test and pelvic girdle questionnaire (PGQ).Conclusion: On the basis of the result of the study, it was concluded that there is significant pelvic girdlepain in post partum period.